Covalent organic framework-loaded silver nanoparticles as robust mimetic oxidase for highly sensitive and selective colorimetric detection of mercury in blood. Issue 48 (2nd December 2022) - Liu, Qingqing; Xu, Chenchen; Chu, Su; Li, Shuai; Wang, Fengxiang; Si, Yanmei; Mao, Guojiang; Wu, Choufei; Wang, Hua
Abstract : Silver-deposited COFs were used as the oxidase mimics for the catalysis-based colorimetric detection of Hg 2+ ions. Abstract : Covalent organic frameworks (COFs) were fabricated with a hierarchical flower-like hollow structure, possessing a large specific surface area, high porosity, and excellent environmental stability. In situ growth of noble silver nanoparticles (AgNPs) onto COFs was conducted yielding COF–Ag nanozymes. The structural advantages of COFs can ensure the uniform dispersion and effective size control of AgNPs. More interestingly, the oxidase-like catalytic activity of the obtained COF–Ag nanozymes could be enhanced in the presence of Hg 2+ ions, which could specifically interact with AgNPs to form Ag–Hg alloys. A COF–Ag catalysis-based colorimetric platform was thereby constructed for highly selective and sensitive analysis of Hg 2+ ions, showing a linear concentration range from 0.050 to 10.0 μM, with a limit of detection of about 3.7 nM. Besides, the developed colorimetric strategy was successfully applied for detecting Hg 2+ ions in human blood with favorable detection recoveries, indicating its potential for applications in the biomedical analysis, environmental monitoring, and food safety fields.